The Influence of Compensation, Work Motivation, and Organizational Culture on Employee Performance at Bali Bistro in ITDC the Nusa Dua Bali - PUTRA, I Wayan Budiartana; SORAYA, Dewi; MEITRI, Ida Ayu Sri (PT Batara Swastika Harati, 2023)
This study aims to determine and analyze the influence of compensation, work motivation and organizational culture on employee performance at Bali Bistro at ITDC The Nusa Dua, Bali. Research data was collected by distributing questionnaires. The total sample was 32 respondents. The analysis tool uses Multiple Linear Regression analysis. Based on the results of the significance test using the F test, it shows that funding, work motivation and organizational culture simultaneously have a positive and significant effect on employee performance at Bali Bistro at ITDC The Nusa Dua, Bali. The coefficient of determination shows that changes in employee performance variables can be explained by the variable availability, work motivation and organizational culture by 83.6%. while 16.4% is explained by other variables outside of compensation, work motivation and organizational culture. Based on the significance test using the t test, it shows that individual interference has a positive and significant effect on employee performance, individual work motivation has a positive and significant effect on employee performance, and organizational culture has a positive and significant effect on employee performance at Bali Bistro.